Cultural Globalization and Music. African Artists in Transnational Networks. Nadia Kiwan and Ulrike Hanna Meinhof. 2011. Palgrave Macmillan. 272 pp. - Erlmann, Veit (International Library of African Music, 2012)
pages: 172-174
Keywords: African Music